LINC-PINT: A Distinctive Long Non-Coding RNA Functioning as a Potential Suppressor in Tumorigenesis - Li, Jiayi; Pan, Yining; Li, Songqiang; Chen, Cheng; Yuan, Chengfu (Current Topics in Medicinal Chemistry, 2025)
<span class=
Keywords: tumorigenesis